A memory of light - Jordan, Robert, 1948-2007; Sanderson, Brandon (Jordan, Robert, 1948-2007. Wheel of time, 2013)
"In the Field of Merrilor the rulers of the nations gather to join Rand al'Thor or to stop him, in Andor the Trollocs seize Caemlyn, in the wolf dream, Perrin Aybara battles Slayer, Mat Cauthon visits his wife in Ebou Dar and all humanity is in peril. The Wheel of Time is turning, and the Age is coming to its end. The Last Battle will determine the fate of the world."--